The relationship between Malaysian preuniversity student-athletes mental health and future career planning - Wan Jaafar, Wan Marzuki; Ismail, Asmah; Abdullah, Muhammad Nazrul Hakim; Omar Dev, Roxana Dev; Sulaiman, Tajularipin; Kai, Yan Wong (South East Asia Association for Institutional Research, 2024)
An athlete's life is full of stress and pressure, as they are more susceptible to stressors like injuries, performance pressure, high expectations, and other difficulties during the transition from an active athlete to retirement. Eventually, student-athletes may withdraw from schools, or drop out from athletic program, which is a great loss to the country. Therefore, this study aimed to investigate the relationship between mental health and career planning—career optimism, career adaptability, career knowledge, college and career readiness self-efficacy and self-efficacy planning—among current Malaysian pre-university student-athletes. This study was conducted in a quantitative manner and employed a Pearson correlation study design. Pre-university student-athletes were selected and three hundred and eighty-nine (389) completed questionnaires were collected for data analysis using the Mental Health Continuum-Short Form (MHC-SF) and Career and Tertiary Education Readiness Inventory (CaTERI). Results revealed that student-athletes’ mental health positively correlated with career planning. These findings can be used to assist and guide the development of career planning or skill enhancement programs for Malaysian pre-university student-athletes.